Threshold concepts and pedagogic representation. Issue 5 (13th June 2016) - Meyer, Jan H.F.
Abstract : Purpose: – The purpose of this paper is to present a brief exposure to the development of the threshold concepts framework (TCF), the intention being to illuminate for interested readers a broader landscape of research activity than that perhaps conveyed by the individual contributions to this special edition. Design/methodology/approach: – There is first an account of how the notion of a "threshold concept" was presented by Meyer and Land in their seminal 2003 paper, and a clarification of some terminology used by them at that time to describe the (confusing for some) "characteristics" of such a concept. A discursive account, with examples, follows on how analyses for, and of, threshold concepts might proceed, and how findings might provoke a reappraisal of associated learning and teaching practices. Towards this end a contemporary pedagogical perspective is introduced based on the construct of integrated threshold concept knowledge (ITCK) as proposed by Meyer and Timmermans (2016). Reference to a detailed case study illustrates the practical dynamics of generating ITCK; specifically in the context of a third-year engineering course embedding the threshold of "critical flow". Activities and processes, transferable to other discipline contexts, are described that yield particular elements of ITCK (different constituent "types of knowledge") in relation, in this case, to "critical flow". A final consideration is the "representation" of "critical flow" for pedagogical purposes in the form of a metacognitive activity for learning and formative assessment purposes that is, again, adaptable to other discipline contexts. Findings: – There are no specific findings in this paper as its purpose is to provide a condensed review of the development of the TCF. Originality/value: – This value of this paper is that it provides a contemporary expert exposure to the development of the TCF by the originator of the notion of a threshold concept.